A Study of Skin Diseases and S.T.D.- At Shree Birendra Hospital - Rajbhandari, Sudarshan Lal (Medical Journal of Shree Birendra Hospital, 1999)
A Study of Skin Diseases and S.T.D.- At Shree Birendra Hospital